A comprehensive microstructural and transmission analysis on oxide dispersion-strengthened (ODS) alloys: Impact of erbium oxide (Er2O3) concentration on physical, structural, gamma-ray, and neutron attenuation properties - Gunoglu, Kadir; Guler, Seval Hale; Guler, Omer; Almisned, Ghada; Ozkavak, Hatice Varol; Albayrak, Muhammet Gokhan; Tekin, H. O. (Elsevier Sci Ltd, 2024)
This study explores the impact of integrating varying concentrations of Erbium Oxide (Er2O3) into Oxide Dispersion Strengthened (ODS) alloys, specifically focusing on gamma-ray and neutron attenuation properties. Utilizing a 316L stainless steel matrix, Er2O3 was methodically incorporated in concentrations ranging from 1 % to 21 % by weight. The structural and radiation attenuation properties of the resultant alloys were comprehensively analyzed using techniques such as X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and experimental gamma-ray transmission studies. The results demonstrate a significant enhancement in gamma-ray shielding with increased Er2O3 content. This enhancement is quantitatively evidenced by increased linear attenuation coefficient, elevated effective Electron Density (Neff), reduced Half-Value Layers (HVL), and higher effective atomic numbers (Zeff). These findings are crucial for nuclear applications where efficient gamma-ray shielding is paramount. Conversely, a decrease in the effective removal cross section (sigma R) for neutron attenuation was observed with higher Er2O3 concentrations. This suggests a potential compromise in neutron shielding efficiency, attributed to the dilution of neutron-absorbing base elements in the alloy. Additionally, the study reveals notable changes in the microstructural properties of the alloys, including alterations in particle size, distribution, and agglomeration, influenced by varying Er2O3 concentrations. In conclusion, this research provides valuable insights into the design of ODS alloys for nuclear radiation shielding, highlighting the balance between gamma-ray attenuation and neutron shielding properties. The study's findings contribute to the development of advanced materials for safer and more efficient nuclear technology applications.
Keywords: Gamma-ray attenuation; Neutron attenuation; 316L stainless steel; Oxide dispersion strengthened (ODS) alloys